PENGARUH PENGGUNAAN MODEL PROJECT BASED LEARNING BERBANTUAN VIDEO DOKUMENTER TERHADAP KEMAMPUAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMA AR RAHMAN MEDAN - Dwi Ningsih, Windi; Prihasti Wuriyani, Elly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the use of the Project Based Learning (PjBL) model assisted by documentary video on the ability to write biographical texts of tenth-grade students at SMA Ar Rahman Medan. This research is motivated by the low ability of students in writing biographical texts, particularly in understanding the text structure and linguistic features, as well as the learning process that is still teacher-centered and lacks the use of engaging instructional media. This study employed a quantitative method with an experimental design of two group post-test only design. The population of this study consisted of all ten grade students of SMA Ar Rahman Medan in the 2025/2026 academic year, totaling 40 students, and all were taken as the sample using a saturated sampling technique. The research instruments were a biographical text writing test and an observation sheet. The data analysis techniques included normality test, homogeneity test, and hypothesis testing. The results showed that the mean score of the experimental class was 80.73, which was higher than that of the control class, 74.44. Based on hypothesis testing, the value of tcount was 2.13 and ttable was 2.02 at a significance level of 0.05, indicating that tcount > ttable. Therefore, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It can be concluded that the use of the Project Based Learning model assisted by documentary video has a significant effect and is effective in improving students’ ability to write biographical texts.